Feasibility of a Vertically Integrated Teaching Strategy during a Surgical Clerkship Event-Learning Methods Matter - Miklos C. Fogarasi; Christine Van Cott; Richard S. Feinn; Steven A. Hirshorn; Eugene H. Lewis; Susan V. Fernandez; Lori Ratchelous; Julia A. O'Connor; Larry D. Gruppen (MDPI AG, 2022)
Sound foundational knowledge improves disease conceptualization and clinical diagnosis. Vertical integration (VI) is an appealing educational strategy to refresh relevant pre-clinical information during clinical rotations. However, an optimal learning approach for this has not yet been established. We hypothesized that a small group collaborative discussion format might serve as an appealing learning method to deliver integrated material and increase retention. During AYs 2018/2019 and 2019/2020, our multidisciplinary team utilized a Colorectal Cancer workshop incorporating pre-clinical material for Y3 students on Surgical Clerkship. In search of an optimized way to deliver vertically integrated content, we alternately presented the workshop material either in a small group (SG) case-based collaborative format or as a standard-sized group (StdG) exercise. We achieved this by testing immediate and late (4-week post-event) recall and assessing student satisfaction with the VI strategy in both physical settings (StdG and SG). A total of 93% of participants considered VI-based training worthwhile, 96% reported an increased knowledge base and 93% would welcome similar VI events in the curriculum. Significantly more SG students than StdG (52% vs. 31%, p = 0.014) enthusiastically endorsed their event and would prefer to have future VI events delivered in the format they experienced (88% for SG vs. 42% for StdG) (p < 0.0001). Combined (immediate + late) recall scores were significantly better in SG versus StdG (p = 0.007), while the rate of attrition at 4 weeks did not differ significantly (p = 0.81). VI strategy successfully reactivated pre-clinical concepts, achieving both high content retention and learner satisfaction during this workshop. Students endorsed future VI events, especially when delivered in a case-based, interactive SG setting. Although resource intensive, a VI strategy employing a small-group collaborative learning method may be considered for broader curricular use in undergraduate medical education.